Site map  

How to calculate G-Y from R-Y and B-Y

The black and white signal Y is defined as 0.299 * Red + 0.587 * Green + 0.114 * Blue.
Or with more rounded numbers: Y = 0.30 * R + 0.59 * G + 0.11 * B.

Let's look at;

 0.299 * (R-Y) + 0.587 * (G-Y) + 0.114 * (B-Y) = ?

Or, with more rounded numbers;

 0.30 * (R-Y) + 0.59 * (G-Y) + 0.11 * (B-Y) = ?

This is the same as;

 0.30*R - 0.30*Y + 0.59*G - 0.59*Y + 0.11*B - 0.11*Y 

Grouping the Y-bits together;

 0.30*R + 0.59*G + 0.11*B - (0.30*Y + 0.59*Y + 0.11*Y)

And since 0.30 + 0.59 + 0.11 = 1;

 0.30*R + 0.59*G + 0.11*B - Y 

And Y is defined as 0.30*R + 0.59*G + 0.11*B. So it actually says 'Y - Y'! Which of course is zero.
And therefore;

 0.30 * (R-Y) + 0.59 * (G-Y) + 0.11 * (B-Y) = 0

If we subtract '0.30 * (R-Y)' and '0.11 * (B-Y)' at both sides of the equal sign we get;

 0.59 * (G-Y) = -0.30 * (R-Y) -0.11 * (B-Y)

Next divide both sides by 0.59;

  0.59               0.30             0.11
 ────── * (G-Y) = - ────── * (R-Y) - ────── * (B-Y)
  0.59               0.59             0.59

Which yields;

 G-Y = - 0.51 * (R-Y) - 0.19 * (B-Y)